The impact of climate change on astronomical observations - Cantalloube, Faustine; Rehfeld, Kira (Nature astronomy, 2020)
Climate change is affecting and will increasingly affect astronomical observations, particularly in terms of dome seeing, surface layer turbulence, atmospheric water vapour content and the wind-driven halo effect in exoplanet direct imaging.
Gesehen am 18.12.2020